Smart contract development and blockchain technology application (3) - Goh, Bryan Hong Xiang (Nanyang Technological University, 2023)
The emergence of decentralized applications was made possible by the founding and implementation of the world's first decentralized ledger system, Blockchain. This emergence offers numerous possibilities to solve real-life problems without relying on a trusted third party. This can be achieved by programming the business logic in smart contracts that will be stored within the Blockchain. Two main features we are tapping on Blockchain would be the elimination of a trusted third party and its tamper-resistant nature. Yet privacy, security concerns arise due to publicly accessible stored data. Scalability is also of another concern since Blockchain is a community of nodes and every node in the network needs to store and process data which is quite computationally heavy. The end goal would be to use Blockchain to prevent data forgery while maintaining decentralization, privacy, security, and scalability.